The collective body: Legacies of monastic discipline in the post-Soviet prison - Azbel, Lyuba (Theoretical criminology, 2022)
The emergence of the prisoner subject is an element of local practices, including how health is governed. Yet, disciplinary practices have been overlooked in research on health in post-Soviet prisons. Drawing on qualitative interviews with 40 male prisoners in Kyrgyzstan, this article performs a genealogical analysis by applying models of subjectivity from Christian monasticism to understand how a healthy body emerges through the contingent governing relations of the post-Soviet prison. An apparatus of “collective self-governance” produces bodies that extend the self to the collective and blur the boundaries between physical and moral health. Here, unlike in the West, the idealization of an autonomous subject is inimical to agency and, by extension, health. Rather, a healthy body is produced through a healing process that rests on submission to the collective, with the threat of exile imminent. In such settings, health interventions aimed at the individual are unlikely to succeed without a consideration of collective healing practices.